An Early Year History of Emergence of Multidrug-Resistant Staphylococcus aureus in West Bengal: A Review: Life Sciences-Microbiology for health care - Kartik Shaw; Sahana Mazumder (International Journal of Life Science and Pharma Research, 2022)
Staphylococcus aureus has been recognized as a causative agent of human diseases for more than 100 years. Staphylococcus aureus can cause numerous fatal diseases including sepsis, soft tissue injury, urinary tract infection. Emergence of multidrug resistance in Staphylococcus aureus is a very common problem worldwide. Multidrug resistant (MDR) bacterium can be identified if the strain is non-susceptible against at least one antibiotic agent in three or more antimicrobial categories. Multidrug resistant Staphylococcus aureus are becoming resistant against various antibiotics like azithromycin, clarithromycin, clindamycin, gentamicin, amikacin, imipenem and other β-lactam antibiotics. Resistance against methicillin and vancomycin can be said as methicillin resistant Staphylococcus aureus (MRSA) and vancomycin resistant Staphylococcus aureus (VRSA) respectively. However, 11% to 56% of the available Staphylococcus aureus are methicillin resistant in West Bengal. Whereas, the emergence of VRSA was found to be equally high in this geographical region. Vancomycin resistant Staphylococcus aureus infections is too hard to treat, as vancomycin is said to be the last resort of antibiotics to treat methicillin resistant Staphylococcus aureus. These emergence of resistance against several antibiotics may include many ways like inhibition of drug entry into the cell, inactivation of β-lactamase enzyme, etc. several genes are also responsible for the drug resistance like mecA, vanH, vanA and vanX. The present review article deals with the research done on the antibiogram of Staphylococcus aureus within the last decade in West Bengal. It also puts light on the various methods by which the Staphylococcus aureus might become resistant against antibiotics and also tries to deals with the genetics involved in it.